Legal Protection for Minors in Burdening Their Own Fixed Assets - Purwiningsih, Septya; Sri Darmadi, Nanang (Sultan Agung Notary Law Review, 2024)
This study aims to analyze: 1) The principle of legal protection that applies in cases of applications for the determination of a guardian to encumber immovable property owned by a minor child. 2) The judge's considerations in providing protection for minor children to encumber their immovable property. The approach method in this study is the statute approach. This type of research is included in the scope of normative legal research. The type and source of data in this study are secondary data. obtained from literature studies. The analysis in this study is prescriptive. The results of the study concluded: 1) The principle of legal protection that applies in cases of applications for the determination of a guardian to encumber immovable property owned by a minor child is intended so that the assets of the child under guardianship are not misused by the guardian and as a preventive measure for inheritance disputes. Where this aims to protect the management of assets that are the child's rights to be used for the best interests of the child and can be accounted for when the child is an adult. One form of legal protection is the existence of a supervising guardian. 2) The judge's consideration in providing protection for minors to burden their permanent assets in Determination Number 310/Pdt.P/2019/PN.Pwt. between a person's position as a legal subject and the capacity to act there is a very close relationship, but both are actually two different things. The position as a legal subject or Person is a quality that allows the person concerned to have rights and obligations, while the problem of capacity to act is a problem of authority to exercise the rights and obligations that he has, as an effort to organize / fulfill his interests.